The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/art.41054
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Disease Correlation of Autoantibodies Against p40 Encoded by Long Interspersed Nuclear Elements in Systemic Lupus Erythematosus

Abstract: Objective Long interspersed nuclear element 1 (LINE‐1) encodes 2 proteins, the RNA binding protein p40 and endonuclease and reverse transcriptase (open‐reading frame 2p [ORF2p]), which are both required for LINE‐1 to retrotranspose. In cells expressing LINE‐1, these proteins assemble with LINE‐1 RNA and additional RNA binding proteins, some of which are well‐known autoantigens in patients with systemic lupus erythematosus (SLE). This study was undertaken to investigate whether SLE patients also produce autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 59 publications
1
37
0
1
Order By: Relevance
“…In systemic lupus erythematosus (SLE), anti-double-stranded DNA (anti-dsDNA) autoantibodies are features of active disease and are particularly associated with lupus nephritis, and the identity of the self or foreign antigens that "break tolerance" (leading to anti-dsDNA and other autoantibody specificities) has been a topic of extensive study. In that context, the study described by Carter et al (1), in which they identified reactivity of sera from SLE patients using the 40-kd protein product of the first open-reading frame (ORF) of the human long interspersed nuclear element 1 (LINE-1) retroelement, is of great interest.…”
Section: Reactivity Of Igg With the P40 Protein Encoded By The Long Imentioning
confidence: 99%
See 1 more Smart Citation
“…In systemic lupus erythematosus (SLE), anti-double-stranded DNA (anti-dsDNA) autoantibodies are features of active disease and are particularly associated with lupus nephritis, and the identity of the self or foreign antigens that "break tolerance" (leading to anti-dsDNA and other autoantibody specificities) has been a topic of extensive study. In that context, the study described by Carter et al (1), in which they identified reactivity of sera from SLE patients using the 40-kd protein product of the first open-reading frame (ORF) of the human long interspersed nuclear element 1 (LINE-1) retroelement, is of great interest.…”
Section: Reactivity Of Igg With the P40 Protein Encoded By The Long Imentioning
confidence: 99%
“…In addition, LINE‐1 nucleic acid can induce type I interferon (IFN), a key pathogenic mediator in SLE . In that regard, the data from Carter and colleagues’ study support the notion of a relationship between high levels of IgG anti‐p40 and a high type I IFN score . The RNP particles that contain LINE‐1 p40, associated LINE‐1 RNA, and DNA, as well as a multitude of proteins that have been implicated as autoantigens in systemic autoimmune diseases , should be priority targets for detailed study of the mechanisms through which the viral remnants in our genomes might act as initiators of autoimmunity.…”
mentioning
confidence: 95%
“…Essentially all patients with SLE have IgG autoantibodies against ORF1p [ 107 , 108 ], which correlate with disease activity measured by the SLE disease activity index (SLEDAI), the presence of lupus nephritis, complement consumption, increased anti-dsDNA, and higher type I IFN activity [ 107 ]. Importantly, there anti-ORF1p autoantibodies do not represent anti-DNA reactivity, as free dsDNA did not compete (while free ORF1p did), DNase treatment did not affect them (while it eliminated anti-dsDNA reactivity), and ORF1p was recognized even when mixed with whole cell lysates.…”
Section: How L1 Retrotransposons May Trigger Ifn-positive Slementioning
confidence: 99%
“…As we recently demonstrated, the titers of IgG autoantibodies against L1 ORF1p correlate significantly with disease phenotypes, SLEDAI, markers of disease activity, and IFN score [ 107 ]. These autoantibodies could conceivably aid in the diagnosis and prognosis of the disease, perhaps guiding which endotype of SLE an individual patient has and, hence, which treatment regimen might be most effective.…”
Section: How L1 Retrotransposons May Trigger Ifn-positive Slementioning
confidence: 99%
“…Various assays have been established to detect RT activity in cells, whether deriving from L1 ORF2p or HERV pol genes [175][176][177]. Using RT-qPCR to assay changes in expression of interferon-stimulated genes may also reveal autoinflammatory effects of retrotransposon misregulation, as described above for AGS and some other autoimmune conditions [137,[178][179][180].…”
Section: Testing the Hypothesismentioning
confidence: 99%